The Safety and Efficacy of Ultrasound-Accelerated-Catheter-Directedthrombolysis with Urokinase in Patients with Intermediate-High Risk Pulmonary Embolism - Al-Terki, Hani; Paulus, Tobias; Gotzmann, Michael; Mügge, Andreas (Cardiology and Cardiovascular Medicine, 2023)
Background: Ultrasound-accelerated-thrombolysis (USAT) represent a safe and effective therapeutic modality in patients with intermediate-tohigh risk pulmonary embolism. The tested thrombolytic agent in all studies investigating USAT in PE patients is alteplase (Actilyse). Actually, there is a lack of supply of alteplase (alteplase®, Boehringer Ingelheim) in Europe. Methods: Nine patients with intermediate-to-high risk pulmonary embolism were treated with USAT and urokinase (300,000 units per catheter over 10 hours) at our institution. Systolic pulmonary artery pressure, right ventricle function and right ventricle/left ventricle ratio were measured at baseline and after therapy. The primary outcome was the difference in the RV/LV ratio from baseline to 24 hours. Safety outcomes included in-hospital death, major and minor bleeding according to GUSTO bleeding score. Results: The mean RV/LV ratio was reduced from 1.19±0.11 at baseline to 0.75±0.29 at 24 hours (p=0.003); the systolic pulmonary artery pressure decreased from 52.4±18.7 to 35.11±8.0 mmHg (p=0.021). There was 1 major access-site bleeding and no in-hospital deaths. During a follow-up of 117.8±72.5 days, no recurrent venous embolism occurred. Conclusion: USAT with Urokinase seems to be safe and effective in patients with intermediate-to-high risk pulmonary embolism with favourable clinical, echocardiographic and laboratory results.